1996
DOI: 10.1016/0014-5793(96)00040-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of opsonized HIV entry in normal B lymphocytes

Abstract: Using our in vitro model of normal B cell infection that functions with low doses of HIV but requires virus opsonization by seropositive patient serum, and complement, we analyzed what receptors allowed virus entry. Here, we show that HIV infection of B cells occurs through 2 major receptors: the CD4 antigen and the CRIICR2 complex. These 2 pathways work independently since a complete inhibition of virus entry requires both CD4 and CD211CD35 blockade on CD4 d~ tonsiHar B cells whereas only the latter is critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…Another possibility is that HIV directly causes alterations in T lymphocytes. This hypothesis is supported by the observation that the virus can infect also B cells probably through two major receptors: CD4 and CD21/ CD35 complex [25]. Moreover, the outer envelope glycoprotein of HIV gp120 functions as a B cell superantigen and triggers polyclonal B cell activation inducing hypergammaglobulinemia and autoantibody production [26].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Another possibility is that HIV directly causes alterations in T lymphocytes. This hypothesis is supported by the observation that the virus can infect also B cells probably through two major receptors: CD4 and CD21/ CD35 complex [25]. Moreover, the outer envelope glycoprotein of HIV gp120 functions as a B cell superantigen and triggers polyclonal B cell activation inducing hypergammaglobulinemia and autoantibody production [26].…”
Section: Discussionsupporting
confidence: 54%
“…The presumptive role of CD21 in B cell activation favors this hypothesis, since modulation of CD21 by immune complexes is a probable mechanism of CD21 involvement in B cell activation, and HIV+ patients are known to have polyclonal B cell activation and increased levels of immune complexes and complement breakdown products [33]. Alternatively, the recent observation that HIV infection of B cells probably occurs through CD21 molecule, suggests a specific downmodulation following HIV entry in B lymphocytes [25]. A similar mechanism is probably involved in CD4 downmodulation after T helper cell infection [10].…”
Section: Discussionmentioning
confidence: 89%
“…Many authors have analyzed the role of complement in HIV infection (5,7,30,31), but to date only a few studies have addressed the adherence of HIV to erythrocytes (6,32,33). Lachgar et al (33) suggested that the Duffy Ag on the membrane of erythrocytes, which is a chemokine receptor, may serve as a binding site for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Covalent binding of C3 fragments to the viral envelope allows binding of HIV to cells expressing receptors for C3b (complement receptor (CR) 2 1, CD35), iC3b (CR3, CD11b/CD18; CR4, CD11c/ CD18), and C3d, C3dg (CR2, CD21). HIV-1 infection of human lymphocytes and monocytes/macrophages is greatly enhanced by opsonization of the virus with complement (3)(4)(5).…”
mentioning
confidence: 99%